Pelanggaran Kode Etik Advokat Pada Kasus Konten Asusila Hotman Paris (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The advocate's code of ethics also binds advocates to behave to maintain the dignity and good name of their profession. Violations of the code of ethics by well-known advocates such as Hotman Paris are a clear example that violations of professional ethics can harm the good name of the advocacy profession as a whole. This research uses normative juridical research methods with literature study. This research uses a case approach, namely cases of violations of the code of ethics committed by Hotman Paris. The results of the research show that even though they are free and independent law enforcers, advocates are still bound by the advocate's code of ethics which sets ethical and moral standards in carrying out their profession. The heavy disciplinary sanctions received by Hotman Paris reflect the seriousness of this violation of the ethical norms of the advocate profession. Even though Hotman Paris left the Indonesian Advocates Association, disciplinary sanctions remain in effect because they are related to violations of the advocate's code of ethics involving the Supreme Court.